Non‐neoplastic anal sac disorders in UK dogs: Epidemiology and management aspects of a research‐neglected syndrome. (1st March 2021) - O'Neill, Dan G.; Hendricks, Anke; Phillips, Jennifer A.; Brodbelt, Dave C.; Church, David B.; Loeffler, Anette
Abstract: Background : Non‐neoplastic anal sac disorders (ASD) are frequent presentations for dogs in primary‐care practice but evidence‐based information on disease occurrence and risk is sparse. This study estimates prevalence, breed associations and other risk factors as well as reporting on clinical management. Methods : A cohort study of dogs attending VetCompass practices between 1 January 2013 and 31 December 2013. Risk factor analysis used multivariable logistic regression methods. Results : Of 104, 212 dogs attending 110 UK practices, the 1‐year period prevalence of ASD was 4.40% (95% CI: 4.22–4.57). Compared to crossbreds, six breeds showed increased odds of ASD (Cavalier King Charles spaniel, King Charles spaniel, Cockapoo, Shih‐tzu, Bichon Frise and Cocker spaniel), and six breeds showed reduced odds (Labrador Retriever, Border collie, Staffordshire Bull Terrier, Lurcher, German Shepherd Dog and Boxer). Brachycephalic types had 2.6 times the odds for ASD compared to dolichocephalic types. Medication prescribed for ASD included antimicrobials (n = 480, 20.24%) and analgesics (n = 284, 11.97%). Anal sacculectomy was performed in under 1% of cases. Conclusions : High prevalence, strong breed predispositions and evidence of severity suggested from the antimicrobial and analgesic therapies combined with current substantial knowledge gaps identify ASD as a key research‐neglected syndrome in dogs.